Sales Program With Comic In Stores PQRUsing Microsoft Visual Basic 6.0 - Sopiani Sopiani (Jurnal Manajemen Informatika, 2010)
Microsoft Visual Basic 6.0 is one of the software used for data processing. The dataprocessing is carried out is equipped with a database as a place to store the data.S c i e n t i f i c wr i t i n g i s a b o u t a c omi c s a l e s p r o g r am i n s t o r e PQR, wherethe author tries to present how the computerization in store goo d and prov idef a c i l i t i e s t o pro c e s s t he da t a - da t a in t he s to r e With the comics in shop salesprogram created by PQRusing Visual Basic 6.0 is expected to be useful in improving performance from theemployees. This is because the performance of the employees can not be separated from data andinformation quickly and accurately so that the time needed to be more slightly.